Mechanistic aspects of the evolution of 3D cholesterol crystallites in a supported lipid membrane via a quartz crystal microbalance with dissipation monitoring - Ma, Gamaliel Junren (2022)
The irreversible formation of cholesterol monohydrate crystals within biological membranes is the leading cause of various diseases, including atherosclerosis. Understanding the process of cholesterol crystallization is fundamentally important and could also lead to the development of improved therapeutic strategies. This has driven several studies investigating the effect of the environmental parameters on the induction of cholesterol crystallite growth and the structure of the cholesterol crystallites, while the kinetics and mechanistic aspects of the crystallite formation process within lipid membranes remain poorly understood. Herein, we fabricated cholesterol crystallites within a supported lipid bilayer (SLB) by adsorbing a cholesterol-rich bicellar mixture onto a glass and silica surface and investigated the real-time kinetics of cholesterol crystallite nucleation and growth using epifluorescence microscopy and quartz crystal microbalance with dissipation (QCM-D) monitoring. Microscopic imaging showed the evolution of the morphology of cholesterol crystallites from nanorod- and plate-shaped habits during the initial stage to mostly large, micron-sized three-dimensional (3D) plate-shaped crystallites in the end, which was likened to Ostwald ripening. QCM-D kinetics revealed unique signal responses during the later stage of the growth process, characterized by simultaneous positive frequency shifts, nonmonotonous energy dissipation shifts, and significant overtone dependence. Based on the optically observed changes in crystallite morphology, we discussed the physical background of these unique QCM-D signal responses and the mechanistic aspects of Ostwald ripening in this system. Together, our findings revealed mechanistic details of the cholesterol crystallite growth kinetics, which may be useful in biointerfacial sensing and bioanalytical applications.